Mechanism Underlying Triple VEGFR Inhibitor Tivozanib-Induced Hypertension in Mice Model - Wael A. Alanazi; Abdulrahman S. Alanazi; Doaa M. El-Nagar; Abdullah M. Aljuraybah; Sary Alsanea; Metab Alharbi (MDPI AG, 2023)
Tivozanib is a triple vascular endothelial growth factor receptor inhibitor, recently approved for the treatment of refractory advanced renal cell carcinoma. Clinical studies showed that around 46% of patients who received tivozanib suffer from hypertension in all grades. Thus, the present study was conducted to identify the role of angiotensin-II (AngII) in the mechanism underlying tivozanib-induced vascular toxicity and hypertension. C57BL/6 male mice received tivozanib (1 mg/kg) with or without losartan (10 or 30 mg/kg) for 3 weeks. Blood pressure was recorded every 3 days, and proteinuria was measured every week. On day 21, all mice were euthanized, and samples were harvested for further analysis. Tivozanib elevated blood pressure until systolic blood pressure reached 163 ± 6.6 mmHg on day 21 of treatment with low urination and high proteinuria. AngII and its receptors, endothelin-1, and oxidative stress markers were significantly increased. While nitric oxide (NO) levels were reduced in plasma and aortic tissues. AngII type 1 receptor blockade by losartan prevented these consequences caused by tivozanib and kept blood pressure within normal range. The results showed that AngII and ET-1 might be potential targets in the clinical studies and management of hypertension induced by tivozanib.